Pemanfaatan Pekarangan Melalui Pengembangan Lanskap Produktif di Desa Mangunan, Kabupaten Bantul Yogyakarta - Siti Nurul Rofiqo Irwan; Rohlan Rogomulyo; Sri Trisnowati (Jurnal Ilmu Pertanian Indonesia, 2018)
Utilization of land around a house as a pakarangan supports the quality and biodiversity of ecosystems. Utilization of pekarangan will develop a productive landscape in order to support food production for household and social interaction facility with neighbors. Mangunan Village has a category of marginal land because of the character of a dry land, rocky, far from water sources, and hilly topography. Therefore this village needs plants that can be adaptable for the environmental characteristics. The research aimed to identify the utilization of pekarangan, to find out the opinions of the people through the utilization of pekarangan and to reveal the linkage of plant functions in developing a productive landscape of pekarangan. Data were collected by purposive sampling with samples of 180 households spreading over six clusters of dusun in Mangunan Village. Variables of research were land area, species and quantity of plants, and people response in developing the productive landscape. Utilization of pekarangan in a wide variety of planting covering planting fruit crops (31%), herbal plants (20%), aesthetics plants (15%), and vegetables (15%). Mangunan Village has diversity index of pekarangan on medium rate (H’ 2.65) and evenness of species on stable position (E 0.32). Therefore, Mangunan Village requires more plants and species to keep a better ecosystem. Community in Mangunan Village was very enthusiastic in the utilization of pekarangan for provisioning food (59%). People require assistance to implement pekarangan functions because they have not enough knowledge on pekarangan plan. The plant functions had high linkage and low linkage in developing productive landscape of pekarangan.